Outpatient Registry REGION: Prospective Follow-up Data and Outcomes in Patients After Acute Cerebrovascular Accident - M. M. Loukianov; S. S. Yakushin; S. Yu. Martsevich; A. N. Vorobyev; K. G. Pereverzeva; E. Yu. Okshina; A. V. Zagrebelnyy; V. G. Klyashtorny; E. V. Kudryashov; S. A. Boytsov; O. M. Drapkina (Столичная издательская компания, 2020)
Aim. To estimate outcomes and risk of all-cause mortality, cardiovascular (CV) mortality, and non-fatal CV events in patients with a history of acute cerebrovascular accident (ACVA) according to data of outpatient prospective registries.Material and methods. 986 patients with a history of ACVA (aged 70.6Ѓ}10.9 years; 56.8% women) were enrolled into the outpatient registry REGION-Ryazan, including the registry of patients with ACVA of any remoteness (ACVA-AR) - 511 (aged 70.4Ѓ}10.5 years; 58.5% women) and the registry of patients, visited outpatient clinics for the first time after ACVA (ACVA-FT) - 475 (aged 70.8Ѓ}11.3 years; 54.9% women). Outcomes, risk of all-cause and CV mortality, composite CV endpoint (CV death, nonfatal myocardial infarction and ACVA), hospitalizations due to CV diseases (CVD) were evaluated during 37 (17;52) months of follow-up period.Results. 310 (31.2%) patients died during the follow-up. The most part of fatal outcomes (56.4%) was registered during the first year of follow-up, especially during the first 3 months (33.9%). Mortality among men (35.9%) was higher than among women (28.0%), р=0.008. 147 (28.8%) and 163 (34.3%) patients died in registries ACVA-AR and ACVA-FT, respectively (70.4% and 90.2% of fatal outcomes were from CV causes, respectively; р=0.04). The higher risk of death was associated with the following factors: age - hazard ratio (HR) 1.10 for each next year of age (95% confidence interval [95%CI] 1.09-1.12); sex (men) - HR 2.01 (95%CI 1.55-2.62); atrial fibrillation (AF) - HR 1.42 (95%CI 1,09-1,86); recurrent ACVA - HR 1.64 (95%CI 1.23-2.19); history of myocardial infarction (MI) - HR 1.45 (95%CI 1.09-1.93); low blood hemoglobin level - HR 2.44 (95%CI 1.59-3.79); heart rate ≥80 beats/min - HR 1.51 (95%CI 1.13-2.03); diabetes - HR 1.56 (95%CI 1.16-2.08); chronic obstructive pulmonary disease (COPD) - HR 1.89 (95%CI 1.34-2.66); no antihypertensive therapy in arterial hypertension - HR 2.03 (95%CI 1.42-2.88). The lower risk of death was associated with the following factors: prescription of ACE inhibitors (ACEI) - HR 0.60 (95%CI 0.42-0.85); angiotensin II receptor blockers (ARB) - HR 0.26 (95%CI 0.13-0.50), beta-blockers - HR 0.71 (95%CI 0.50-0.99); statins - HR 0.59 (95%CI 0.42-0.82). Factors, listed above, had significant association not only with all-cause mortality but also with CV mortality and composite CV endpoint. The higher rate of hospitalizations due to CVD was associated with younger age (incidence rate ratio [IRR] for 1 year 1.03; 95%CI 1.02-1.05; р<0.001), female sex (IRR 2.40; 95%CI 1.79-3.23; р<0.001), COPD (IRR 2.44; 95%CI 1.63-3.65; р<0.001) and heart rate ≥80 beats/min (IRR 1.51; 95%CI 1.12-2.04; р=0.007).Conclusions. All-cause mortality in patients with a history of ACVA, enrolled in outpatient registry REGION, was 31.2% during 3-year follow-up. The proportion of CV death among the fatal cases was higher in the ACVA-FT registry than in ACVA-AR registry. The higher mortality rate was associated with the following factors: age, sex (male), recurrent ACVA, history of MI, diagnosis of AF, COPD and diabetes, low blood hemoglobin level, heart rate ≥80 beats/min, no antihypertensive therapy in arterial hypertension. The higher incidence of hospitalizations due to CVD was associated with younger age, sex (female), COPD and heart rate ≥80 beats/min. Prescription of ACEI, ARB, beta-blockers and statins was associated with lower risk of death and composite CV endpoint.